Strategic nest site selection in one of the world's largest loggerhead turtle nesting colonies, on Maio Island, Cabo Verde. Issue 2 (1st March 2023) - Patino-Martinez, Juan; Dos Passos, Leno; Amador, Raquel; Teixidor, Arnau; Cardoso, Sergio; Marco, Adolfo; Koenen, Franziska; Dutra, Amanda; Eizaguirre, Christophe; Dierickx, Elisa G.; Tiwari, Manjula; Székely, Tamás; et al.
Abstract: For species without parental care, such as sea turtles, nest site selection is particularly important for embryo development, hatchling survival and, ultimately, reproductive success. We conducted an 8-year (2012–2019) capture–mark–recapture study of the re-nesting behaviour of loggerhead turtles Caretta caretta to identify both inter- and intra-beach patterns of nest site selection. Our study site, Maio Island in the archipelago of Cabo Verde, hosts one of the largest loggerhead turtle nesting colonies globally. Of 1, 060 females analysed, 77% laid repeated clutches within 15 km of their previous nesting sites both between and within nesting seasons. This site fidelity was particularly high (64–71%) for turtles nesting on the east coast of Maio Island. In two areas of the island (north-west and south-east) individual nesting zone consistency was extremely low (10–25%). In all cases extra-zone re-nesting events mainly occurred on the east coast. We also found that females avoided re-nesting near the shoreline, which is particularly relevant in the context of rising sea levels. Overall, loggerhead turtles nesting in Maio Island are philopatric but are using a bet-edging strategy to distribute nests amongst several beaches, choosing the safest area within each beach to maximize their reproductive success. This study highlights the priority sites for protection on Maio Island and could help to optimize capture–mark–recapture programmes. The data reveal the potential for adaptive responses to projected sea level rises.